Digital Citizenship Education: Pancasila As A Source of Digital Ethics in Indonesia - Nurbani Yusuf; Arif Prasetyo Wibowo; Budiono Budiono (JED (Jurnal Etika Demokrasi), 2024)
This research aims to analyze and embody Digital Citizenship Education that makes Pancasila a source of digital ethics in educational institutions. Using descriptive qualitative research methods makes this research up to date with the latest conditions and situations. The informants in this research were Pancasila and Citizenship Education Teachers of Senior High Schools, Principals, and Heads of National Unity and Political Bodies in Malang City. The selection of informants is based on the responsibility and mandate carried out in their expertise. The results of the research Pancasila as an ideology, worldview, and source of all sources in various aspects of the life of society, nation, and state have consequences for digital ethics in today's disruption era. Efforts to embody Pancasila in maintaining its existence must continue to be pursued. So that Pancasila as the philosophy of the nation can continue to answer the challenges of the times. This flexibility dimension is the space to be able to maintain the existence of Pancasila so that it can continue to be grounded, so that the Idealism Dimension and Reality Dimension can continue to be in harmony in accordance with the purpose of the establishment of Independent Indonesia.